Student reference book (Chicago, ill., 2012)
For Grades 3-6, this hardcover resource contains explanations of key mathematical content, with directions to the Everyday Mathematics® games.
Keywords: Toán học,Mathematics; Dạy và học (Tiểu học),Study and teaching (Elementary)